An Eight-State Molecular Sequential Switch Featuring a Dual Single-Bond Rotation Photoreaction - Gerwien, Aaron; Jehle, Benjamin; Irmler, Marvin; Mayer, Peter; Dube, Henry (Journal of the American Chemical Society, 2021)
Typical photoswitches interconvert between two different states by simple isomerization reactions, which represents a fundamental limit for applications. To expand the switching capacity usually different photoswitches have to be linked together leading to strong increase in molecular weight, diminished switching function, and less precision and selectivity of switching events. Herein we present an approach for solving this essential problem with a different photoswitching concept. A basic molecular switch architecture provides precision photoswitching between eight different states via controlled rotations around three adjacent covalent bonds. All eight states can be populated one after another in an eight-step cycle by alternating between photochemical Hula-Twist isomerizations and thermal single-bond rotations. By simply changing solvent and temperature the same switch can also undergo a different cycle instead interconverting just five isomers in a selective sequence. This behavior is enabled through the discovery of an unprecedented photoreaction, a one-photon dual single-bond rotation.
CRIS-Team Scopus Importer:2022-03-04